Conductive polymers containing phenothiazine units in the main chains - Łapkowski, M.; Golba, S.; Żak, J.; Stolarczyk, A.; Sołoducho, J.; Doskocz, J.; Sułkowski, W. W.; Bartoszek, M. (Polimery, 2009)
The results of investigations of conductive polymers made of monomers built of five of six-membered systems (thiophene, furan or pyridine) and phenothiazine (Ph_Het) are reported. Electrochemical properties of the monomers used (Table 1 and 2, Fig. 1-3, 6, 7) and polymeric films, made of them via electro syntheses (Table 3, Fig. 4, 5, 8-11), were evaluated by cyclic voltammetry, UV-Vis spectroscopy and EPR spectroscopy coupled with electrochemical technique. The measurements showed the electro activity of materials. Two-stage oxidation of the monomers (first step - to cation-radical, the other one - to dication) took place in the measured potential range. Voltammetric scanning of the molecules containing heterocyclic thiophene or furan rings led to settling of conductive polymer layer on the surface of working electrode. The deposition of polymer film was not observed in the case of monomer with pyridine rings. Estimated values of (Eg) of conductive polymers layers formed were in the range 2.0-2.5eV.